Sex-specific recombination maps for individual macrochromosomes in the Japanese quail (Coturnix japonica) - del Priore, Lucía (2015)
Meiotic recombination in the Japanese quail was directly studied by immunolocalization of mutL homolog 1 (MLH1), a mismatch repair protein of mature recombination nodules. In total, 15,862 crossovers were scored along the autosomal synaptonemal complexes in 308 meiotic nuclei from males and females. Crossover frequencies calculated from MLH1 foci show wide similitude between males and females with slightly higher number of foci in females. From this analysis, we predict that the sex-averaged map length of the Japanese quail is 2580 cM, with a genome-wide recombination rate of 1.9 cM/Mb. MLH1 focus mapping along the six largest bivalents showed few intersex differences in the distribution of crossovers along with variant patterns in metacentric and acrocentric macrobivalents. These results provide valuable information to complement linkage map analysis in the species while providing insight into our understanding of the mechanisms of crossover distribution along chromosome arms.